ChemInform Abstract: Synthesis and Biological Evaluation of Novel Substituted 1, 3, 4‐Thiadiazole and 2, 6‐Di Aryl Substituted Imidazo [2, 1‐b][1, 3, 4]Thiadiazole Derivatives. Issue 28 (15th July 2014) - Chandrakantha, B.; Isloor, Arun M.; Shetty, Prakash; Fun, Hoong Kun; Hegde, Gurumurthy
Abstract All products are purified by filtration.